Effects of Gd211 Particles Characteristic in the Precursor Pellets on the Levitation Force of Single-Domain GdBCO Bulks Prepared by the Gd + 011 TSIG Method - Xiaochun Yuan; Wanmin Yang (Advances in Materials Science and Engineering)
In this paper, single-domain GdBCO bulks have been fabricated by a new Gd + 011 TSIG method with precursor solid phase pellets (PSPPs) of different Gd211 particle sizes and distributions, prepared by solid state reaction with well-mixed (Gd2O3 + BaCuO2) pellets at different temperatures. The novel results indicated that (1) the average size of Gd211 particles in PSPP is monotonically increasing with increasing the sintering temperature up to 1200°C. (2) With increasing the sintering temperature from 950 to 1200°C, the porous ratio and the density of the PSPP are, respectively, monotonically decreasing and increasing. Furthermore when the sintering temperature is less than 1000°C, the porous ratio is higher and the density is lower than the values of the pressed pellets. (3) With increasing the sintering temperature, the average size of Gd211 particles in the GdBCO bulk first decreases and then increases. In addition, the smallest Gd211 particles are obtained in the sample sintered at 1050°C. (4) The maximum levitation force is obtained in the sample sintered at 1150°C with a relatively larger size of Gd211 particles and lower porosity. This result is significant when fabricating high-quality GdBCO bulk superconductors by controlling the porosity, Gd211 particle size, and their distribution characteristic.